A novel p-dimethylaminophenylether-based fluorescent probe for the detection of native ONOO− in cells and zebrafish. Issue 17 (2nd August 2021) - Sheng, Wenlong; Wang, Kun; Gao, Na; Wang, Lizhen; Wang, Rongchun; Zhang, Xuanming; Chen, Xiqiang; Zhang, Yun; Zhu, Baocun; Liu, Kechun
Abstract : A fluorescent probe PDPE-PN with prominent sensitivity and specificity, and a fast response towards ONOO − was synthesized and characterized. The probe with good biocompatibility has been successfully applied in cells and zebrafish. Abstract : Peroxynitrite (ONOO − ) is a highly reactive substance, and plays an essential part in maintaining cellular homeostasis. It is crucial to monitor the ONOO − level in cells in normal and abnormal states. We introduced a p -dimethylaminophenylether-based fluorescent probe PDPE-PN, which could be synthesized readily. The new probe had prominent sensitivity and specificity, and a fast response towards ONOO − . The spectral performance of probe PDPE-PN was outstanding and the limit of detection was 69 nM. Probe PDPE-PN with low toxicity was applied to detect endogenous/exogenous ONOO − in RAW 264.7 macrophages and zebrafish. Importantly, successful application of the new receptor opens up new ideas for the design of ONOO − probes.